PELATIHAN DETEKSI ADANYA FORMALIN, BORAKS, DAN PEWARNA BERBAHAYA DALAM MAKANAN SERTA PENYULUHAN BAHAYANYA BAGI KESEHATAN MASYARAKAT DESA MEURANDEH DAYAH KOTA LANGSA - Seprianto, Seprianto; Hasibuan, Molani Paulina; Effendi, Desy Irafadillah (Universitas Muhammadiyah Tapanuli Selatan, 2019)
This Community Service Program aims to train people to make simple tools that can detect the presence of formalin and borax in food so that people are helped in choosing safe food ingredients. The target partners of the training activities were mothers in Meurandeh Dayah Village. Based on preliminary search, partners have not yet realized the dangers of food containing prohibited additives such as formalin, borax and harmful dyes to health. Partners also do not know the simple way to detect the presence of formalin, borax, and forbidden dyes such as Rhodamine B in food. Therefore, the activities carried out include socialization about the dangers of prohibited additives in food and training to make simple tools to detect the presence of formalin and borax using turmeric and toothpicks. The activity continued with the practice of detecting the presence of prohibited additives in food using simple tools that have been made. This activity contributes to improving the level of public health through the skills to choose food that is safe for health.Keywords: training, borax, formalin, harmful dyes, additives.